2007
DOI: 10.1038/sj.jp.7211651
|View full text |Cite
|
Sign up to set email alerts
|

Infant botulism

Abstract: Infant botulism results from the absorption of heat-labile neurotoxin produced in situ by ingested Clostridium botulinum. Honey and environmental exposure are the main sources of acquisition of the organism. Clinical manifestations are owing to progressive neuromuscular blockade, initially of muscles innervated by cranial nerves and later of the trunk, extremities and diaphragm. Presynaptic autonomic nerves are also affected. The diagnosis is made on clinical grounds and is confirmed by recovery of the organis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
64
0
5

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 45 publications
1
64
0
5
Order By: Relevance
“…This is remarkable because honey harbors very low numbers of viable bacteria (Tysset et al 1980;Snowdon and Cliver 1996;Gilliam 1997;Iurlina and Fritz 2005;López and Alippi 2007;Loncaric et al 2009;Kačániová et al 2009) due to its antimicrobial properties (White et al 1963;Molan 1992aMolan , b, 2001Taormina et al 2001;Lusby et al 2005;Gomes et al 2010;Kwakman et al 2010). Exceptions are sporeforming bacteria like P. larvae, causative agent of American Foulbrood (Genersch 2010); C. botulinum, facultative pathogen for humans (Brook 2007); and other spore-forming bacteria primarily Bacillus and relatives (Iurlina and Fritz 2005), which is not inactivated by the inhibitory properties of honey. The representative of PSG4, strain 125, exhibited the highest 16S rRNA gene sequence similarity (98.4%) with the type strain of Stenotrophomonas maltophilia (X95923), and it can be considered as a representative of the genus Stenotrophomonas.…”
Section: Discussionmentioning
confidence: 99%
“…This is remarkable because honey harbors very low numbers of viable bacteria (Tysset et al 1980;Snowdon and Cliver 1996;Gilliam 1997;Iurlina and Fritz 2005;López and Alippi 2007;Loncaric et al 2009;Kačániová et al 2009) due to its antimicrobial properties (White et al 1963;Molan 1992aMolan , b, 2001Taormina et al 2001;Lusby et al 2005;Gomes et al 2010;Kwakman et al 2010). Exceptions are sporeforming bacteria like P. larvae, causative agent of American Foulbrood (Genersch 2010); C. botulinum, facultative pathogen for humans (Brook 2007); and other spore-forming bacteria primarily Bacillus and relatives (Iurlina and Fritz 2005), which is not inactivated by the inhibitory properties of honey. The representative of PSG4, strain 125, exhibited the highest 16S rRNA gene sequence similarity (98.4%) with the type strain of Stenotrophomonas maltophilia (X95923), and it can be considered as a representative of the genus Stenotrophomonas.…”
Section: Discussionmentioning
confidence: 99%
“…"Infant botulism", is associated with anaerobic conditions adequate for ingested spore germination in the intestinal tract of infants under 6 months of age (Brook, 2007). Up to 20 % of the honey specimens from different countries may contain spores of botulinum toxin (Nakano et al, 1990).…”
Section: Botulinum Toxin: From the Most Potent Poison To Clinical Usementioning
confidence: 99%
“…5 Infant botulism is age-related but does not seem to be affected by race or ethnicity; 95% of all cases occur in patients 6 weeks to 6 months of age. 6 More than 1500 cases have been identified in the United States since it was first recognized in 1976, with ∼80 to 100 cases per year currently being reported. 6 A recent publication reviewing the global occurrence of infant botulism found that honey exposure was significantly more common among infants hospitalized outside of the United States.…”
mentioning
confidence: 99%
“…6 More than 1500 cases have been identified in the United States since it was first recognized in 1976, with ∼80 to 100 cases per year currently being reported. 6 A recent publication reviewing the global occurrence of infant botulism found that honey exposure was significantly more common among infants hospitalized outside of the United States. 1 Although Clostridium botulinum spores are known to be found in soils and dust worldwide, most countries have not yet reported cases of infant botulism, suggesting that the disease is either underrecognized and or underreported.…”
mentioning
confidence: 99%